The Role of Job Stress and Organizational Commitment on Turnover Intention of Gen Z Employees in Cirebon with Job Satisfaction as a Mediating Variable - Alyanisa; Mayasafira; Siti Maryam (Jurnal Manajemen (Edisi Elektronik), 2025)
This research investigates the influence of work stress and organizational commitment on the turnover intention of Generation Z employees in Cirebon City, examining the mediating role of job satisfaction. Employing a quantitative approach with an associative design, data were collected via questionnaires from 253 Generation Z employees in Cirebon City and analyzed using Structural Equation Modeling (SEM) with SMART PLS. The findings indicate a positive and significant effect of work stress on turnover intention, while organizational commitment shows a negative but insignificant effect. Work stress has a negative and insignificant impact on job satisfaction, whereas organizational commitment positively and significantly influences job satisfaction. Furthermore, job satisfaction did not mediate the relationship between work stress and turnover intention; however, it did mediate the relationship between organizational commitment and turnover intention. These findings offer implications for organizations seeking to reduce turnover among Generation Z employees by addressing work stress and fostering organizational commitment, considering the role of job satisfaction. Future research could explore other antecedents of turnover intention, such as organizational culture, leadership styles, and career development opportunities. Comparative studies across different industries or regions could also enhance the understanding of this phenomenon.